Spatial features, problems and prospects for formation of united territorial communities in Kharkiv region - Kateryna Kravchenko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
In modern conditions of our country great attention of scientists devoted to the problems of improvement of territorial organization regional settlement systems. The process of decentralization of power creates entirely new conditions for the life of the regions of Kharkiv region. Formation of local communities should be focused on providing the public with maximum number of quality services. In every region of Ukraine there are territories, such as cities, that have a more intense level of development, have better living conditions than the peripheral rural areas. That is why the regional development planning is an important for aligning the economic capacity of the weaker regions on the regional level.